Control and Monitoring System for Livestock Feeding Time via Smartphone - Fakharulrazi, Alyani Nadhiya; Yakub, Fitri (Journal of Sustainable Natural Resources, 2020)
The livestock farming sector usually require a lot of manpower and may face problems such as adhering the designated feeding schedule. Therefore, this paper intends to aid in this sector by bringing the smart feeder system. The main objective of this paper is to control and monitor livestock feeding time using application via smartphones. This is to ensure that the livestock are fed according to the right schedule. This paper also highlited the advantage of the smart feeder system where it can be used to save up money and energy that can be obtained by having less labor workers. This is because of the hopper storage that can accommodate the food up to three days. The importance of this system is its ability to automate the feeding system for the livestock. The smart feed system designed is different from the existing livestock feeding machines that are available anywhere in the market due to the implementation of Internet of Things (IoT) in the system. The usage of IoT allows farmers to set the feeding schedule automatically by using an application via smartphone. Besides, users will also be informed on the weight of food in the storage and food container through the application. This will allow the users to monitor the food storage and only come to refill it when it is empty. Farmers can also observe whether the livestock have eaten or not by getting updated on the level of food of the food storage using an ultrasonic sensor.